Essentials of Spinal Cord Injury Medicine 2018
DOI: 10.5772/intechopen.76857
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Spinal Cord Injury

Abstract: Penetrating spinal cord injury (SCI) is a relatively rare entity affecting mainly young males and military personnel worldwide. These injuries are the source of permanent disabilities to the affected patient and family and have substantial social and economic concerns. This chapter is an overview of the common penetrating spinal cord injuries, their incidence worldwide, causes, primary evaluation, and treatment including medical treatment and late definitive surgical treatment. It also describes common complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Surgical intervention has been demonstrated to reduce delayed complications. Delayed wound infection has been observed in cases managed solely with irrigation and suture [1]. Decompression, laminectomy, and hemilaminectomy are typically required for symptomatic cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical intervention has been demonstrated to reduce delayed complications. Delayed wound infection has been observed in cases managed solely with irrigation and suture [1]. Decompression, laminectomy, and hemilaminectomy are typically required for symptomatic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord injuries (SCI) resulting in lifelong disabilities are a significant societal burden, particularly affecting the working population in their third decade of life [1]. The earliest known record of penetrating SCI dates back to 1700 BC in Egyptian papyrus, while in the second century [2], Greek physician Galen demonstrated that a horizontal cut through the spine of a monkey led to motor and sensory loss below the spinal cord cut [3].…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) and the lifelong disabilities associated with it are of a major concern to the society worldwide (13) . Therefore, in order to provide optimized benefits to current therapies, it is necessary to identify the expression of novel, highly sensitive and specific biomarkers in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features of cervical PSCI result directly from trauma but may also be associated with vascular impairment, which has been reported in autopsies. 4 Depending on the exact site of injury, the most common neurological deficit includes high or low tetraplegia or end up with deep unilateral paresis. 5 When a cutting edge runs between the spinous and transverse process, it may result in Brown-Sequard syndrome.…”
Section: Introductionmentioning
confidence: 99%